2016
DOI: 10.1038/cddis.2016.345
|View full text |Cite
|
Sign up to set email alerts
|

PARP1 regulates the protein stability and proapoptotic function of HIPK2

Abstract: Homeodomain-interacting protein kinase 2 (HIPK2) is a nuclear serine/threonine kinase that functions in DNA damage response and development. In the present study, we propose that the protein stability and proapoptotic function of HIPK2 are regulated by poly(ADP-ribose) polymerase 1 (PARP1). We present evidence indicating that PARP1 promotes the proteasomal degradation of HIPK2. The tryptophan-glycine-arginine (WGR) domain of PARP1 was necessary and sufficient for the promotion of HIPK2 degradation independentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…As apoptosis alteration is responsible, among other effects, of tumor resistance to therapies [ 40 ], the regulation of HIPK2 expression level and activity is of particular relevance for the determination of cell fate between survival and death. Previous studies established that HIPK2 protein stability is tightly regulated by ubiquitin-proteasome system [ 12 14 , 20 22 , 32 , 41 ]. In the present study, we have shown that hyperglycemia promotes the degradation of HIPK2 in parte through ubiquitin ligase Siah2 downstream of a protein cascade including PP2A and HIF-1α, as summarized in the scheme (Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As apoptosis alteration is responsible, among other effects, of tumor resistance to therapies [ 40 ], the regulation of HIPK2 expression level and activity is of particular relevance for the determination of cell fate between survival and death. Previous studies established that HIPK2 protein stability is tightly regulated by ubiquitin-proteasome system [ 12 14 , 20 22 , 32 , 41 ]. In the present study, we have shown that hyperglycemia promotes the degradation of HIPK2 in parte through ubiquitin ligase Siah2 downstream of a protein cascade including PP2A and HIF-1α, as summarized in the scheme (Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…As previous studies established that HIPK2 protein stability is tightly regulated by several ubiquitin ligases acting in different cellular conditions [ 12 14 , 20 22 , 32 , 41 ], we asked what was the link between HG, PP2A and HIPK2 stability. Data from the literature reported that PP2A activation, upon increased glucose flux, induces carbohydrate response element binding protein (ChREBP) dephosphorylation and nuclear translocation to bind to the proximal HIF1A promoter, stimulating its transcription and HIF-1α stabilization even in normoxic condition [ 26 , 52 54 ] (Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…With low-level of DNA damage, PARP1 promotes cell survival by repairing SSBs of DNA and does not permit their progression to toxic double-strand breaks (DSBs) of DNA [ 5 ]. If SSBs of DNA progress to DSBs, PARP1 induces phosphorylation of H2AX (γH2AX) and induces recruitment of BRCA1/2 to repair DSBs, which eventually prevents apoptotic cell death [ 6 , 7 ]. Therefore, PARP1 has a vital role in the survival of damaged cells, and could confer a survival advantage to cancer cells during anti-cancer therapy targeting apoptosis of cancer cells [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…When there are defects in BRCA1/2, inhibition of PARP1 induces accumulation of SSBs which eventually progresses to DSBs that lead to apoptosis [ 4 , 10 , 11 ]. In this context, PARP inhibitors might be promising anticancer drugs in conjunction with DNA repair deficits [ 3 , 4 , 6 , 7 , 12 ]. Therapeutic efficacy of PARP inhibition has been proposed for human papilloma virus-related squamous cell carcinomas and colorectal carcinomas [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The members of the poly-ADP-ribosyltransferase (PARP) family, PARP1 and PARP2, are examples of ARTs that modify proteins interacting with DNA. PARP1 and PARP2 are localized in the nucleus where they are involved in many cellular processes [29][30][31][32]. PARP1 and PARP2 transferase activity is known to be necessary for repair of DNA damage such as deamination, hydroxylation and methylation of nitrogenous bases as well as for repair of single strand breaks.…”
Section: Introductionmentioning
confidence: 99%